Mathematics and Computation in Music First International Conference, MCM 2007, Berlin, Germany, May 18-20, 2007. Revised Selected Papers - Klouche, Timour; Noll, Thomas (Communications in Computer and Information Science, 2009)
This book constitutes the refereed proceedings of the First International Conference on Mathematics and Computation in Music, MCM 2007, held in Berlin, Germany, in May 2007. The 51 papers presented were carefully reviewed and selected from numerous submissions. The MCM conference is the flagship conference of the Society for Mathematics and Computation in Music. The papers deal with topics within applied mathematics, computational models, mathematical modelling and verious further aspects of the theory of music.